THE INTERDISCIPLINARY IMPACT OF ISOTRETINOIN THERAPY ON ACNE VULGARIS: A COMPREHENSIVE REVIEW OF ADVERSE EFFECTS AND MONITORING PROTOCOLS - Woźniak, Liwia (International Journal of Innovative Technologies in Social Science, 2026)
Acne vulgaris is a prevalent chronic inflammatory disease that carries a profound psychosocial burden, often requiring systemic treatment with isotretinoin for severe, nodulocystic, or recalcitrant cases. As the only therapeutic agent targeting all major pathogenic factors, isotretinoin induces sebocyte apoptosis, drastically reducing sebum production by up to 90% and altering the follicular microenvironment. However, this widespread cellular impact results in a broad spectrum of dose-dependent adverse effects. This comprehensive review synthesizes recent clinical, real-world, and pharmacovigilance data to critically evaluate isotretinoin’s interdisciplinary impacts across mucocutaneous, ophthalmic, musculoskeletal, neuropsychiatric, and metabolic systems. Notable side effects include ubiquitous xerosis and cheilitis, dry eye syndrome, myalgia, dyslipidemia, and complex neuropsychiatric challenges, alongside its well-documented teratogenicity. Furthermore, this paper explores evidence-based mitigation strategies to manage these toxicities without compromising efficacy. It highlights how proactive dietary supplementation - such as omega-3 fatty acids to counter hypertriglyceridemia, and L-carnitine to resolve myalgia-can significantly enhance patient tolerability. Additionally, the evolution of dosing protocols, including low-dose and intermittent regimens, alongside novel micronized formulations that overcome strict dietary fat requirements, ensures consistent bioavailability. Ultimately, the paradigm of isotretinoin therapy is shifting towards highly individualized care. By integrating an interdisciplinary approach that includes routine ophthalmic care and psychodermatological screening, clinicians can minimize risks while maximizing the therapeutic benefits and overall quality of life for patients.